Infrastructure development recommendation for traditional market to promote economic growth: A case study of Landungsari traditional market - Rizki Amalia Tri Cahyani; Aulia Indira Kumalasari (Journal of Community Service and Empowerment, 2023)
The Landungsari Traditional Market is intended to serve as a major economic engine for the local area. This community service aims to assist in assessing the conditions of infrastructure and facilities in the Traditional Market of Landungsari since the availability and quality of infrastructure and facilities play a significant role in supporting the sustainable growth of the traditional market. The factors in question include the physical state of the buildings, the availability of utility infrastructure, the availability of essential public facilities, and the market’s accessibility. The study's findings were presented as suggestions for infrastructure improvement that could be used as a guide for the local government to further enhance the market's physical features. Visual assessment revealed that while the market's structure is generally in good condition, several of its components require maintenance and repair. This market needs to make improvements in terms of utility systems since it only satisfies around 25% of the standard requirements. Furthermore, as only 71% of the market's essential public facilities have been provided, additional facility development was necessary. Even though the market's building and facilities have been given adequate access, it is recommended to perform improvements in terms of wider market aisles, the addition of wheelchair-accessible pathways, and the provision of public transportation services to achieve a higher level of market accessibility.